Shaped Omnidirectional Reflector Fed by a Dielectric Lens Associated with a Coaxial Feed Horn - J. R. Bergmann; L. S. Patinos (International Journal of Antennas and Propagation)
The paper explores an omnidirectional antenna configuration composed of a reflector fed by a shaped dielectric lens associated with a coaxial TEM horn. A simple formula describes the lens shape obtained by applying Fermat’s principle to control the rays’ caustic emerging from the dielectric interface. Based on geometrical optics (GO) principles, a synthesis technique defines the reflector shape to control the antenna radiation pattern in the vertical plane. Concatenated conic describes the reflector generatrix. The study employs a full-wave analysis to validate the designs and explores the proposed configuration to attend two distinct far-field specifications.